H+-Assisted fluorescent differentiation of Cu+ and Cu2+: effect of Al3+-induced acidity on chemical sensing and generation of two novel and independent logic gating pathways. Issue 29 (12th March 2015) - Ha, Yonghwang; Murale, Dhiraj P.; Yun, Changsuk; Manjare, Sudesh T.; Kim, Hyungjun; Kwak, Juhyoun; Lee, Yoon Sup; Churchill, David G.
Abstract : A novel logic gate containing protecting groups interacts with various species (acetonitrile) with fluorescence responses relating to ligand non innocence. Abstract : A novel Schiff base probe exhibited strong 'turn-ON' fluorescence for Cu 2+ at 345 nm, Al 3+ at 445 nm, and Cu + at 360 nm in the presence of Al 3+ in organic solvent (acetonitrile), which allowed for construction of molecular logic gates 'INH' and '1:2 DEMULTIPLEXING.' H + generated from Al 3+ contributed greatly to Cu + chemosensing based on a redox non-innocence mechanism.